Direct Neuronal Reprogramming: Achievements, Hurdles, and New Roads to Success - Gascón, Sergio; Masserdotti, Giacomo; Russo, Gianluca Luigi; Götz, Magdalena (Cell stem cell, 2017)
The ability to directly reprogram mature cells to alternative fates challenges concepts of how cell identities are maintained, erased, and acquired. Recent advances in understanding and overcoming hurdles to direct neuronal conversion have provided new insights into mechanisms that maintain cell identity programs and have enabled high efficiency reprogramming in vivo. We discuss key cell-intrinsic molecular and metabolic constraints that influence the establishment of a new identity as well as environmental inputs from injured brains that favor or harm the conversion process. Finally, we outline the challenges ahead with a particular focus on direct neuronal reprogramming in vivo.